Capillary filling in closed end nanochannels - Phan, Vinh-Nguyen (2012)
We investigated the interactions between liquid, gas, and solid phases in the capillary filling process of closed-end nanochannels. This paper presents theoretical models without and with absorption and diffusion of gas molecules in the liquid. Capillary filling experiments were carried out in closed-end silicon nanochannels with different lengths. The theoretical and measured characteristics of filling length versus time are compared. The results show that the filling process consists of two stages. The first stage resembles the capillary filling process in an open-end nanochannel. However, a remarkable discrepancy between the experimental results and the theory without gas absorption is observed in the second stage. A closer investigation of the second stage reveals that the dissolution of gas in the liquid is important and can be explained by the model with gas absorption and diffusion.